2019
DOI: 10.7831/ras.8.0_1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physico-Chemical Properties of Persimmon (<i>Diospyros kaki </i>Thunb.) During Drying and Quality Deterioration During Storage

Abstract: Dried persimmon (Diospyros kaki Thunb.) is one of the most popular fruit products in East Asia, but its properties and consumer acceptance strongly depend on the drying process and storage conditions that are used. The quality of dried persimmon depends on its physical (color, texture) and chemical (tannin levels, sugar content, the presence of white powder on the surface) properties, which are drastically affected by the decrease in moisture content and composition changes that occur during the drying process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The ST values were similar to those of the non-astringent fruit. Tannin insolubilization during the drying process could be associated with structural flesh changes ( Figure 2 ), which happens during natural persimmon fruit ripening [ 2 , 32 , 38 ]. In astringent cultivars, the ripening process is accompanied by gradual tannin insolubilization, which leads to a progressive decline in ST with subsequent astringency reduction [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ST values were similar to those of the non-astringent fruit. Tannin insolubilization during the drying process could be associated with structural flesh changes ( Figure 2 ), which happens during natural persimmon fruit ripening [ 2 , 32 , 38 ]. In astringent cultivars, the ripening process is accompanied by gradual tannin insolubilization, which leads to a progressive decline in ST with subsequent astringency reduction [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…These differences were still found after 81 days (Figure 3c). The color changes that occurred during the drying period were the result of several biochemical reactions, such as degradation of carotenoids, decomposition of other color pigments, and enzymatic and non-enzymatic reactions [32]. Yamada et al (2009) [33] suggested that the oxidative and non-oxidative degradation of ascorbic acid would contribute markedly to the browning of this product type, while enzymatic browning, by polyphenol oxidase, and the Maillard reaction, between amino acids and reducing sugars would not play a key role.…”
Section: Physico-chemical Determinationsmentioning
confidence: 99%
“…Persimmon fruit can be found in several regions on the islands of Java and Sumatra, but fruit grown in the East Java region is of better quality and produced in greater quantity than other regions, especially in the Bumiaji, Ampelgading, and Tirtoyudo regions [23]. Farmers usually soak persimmons in a lime solution or use alcohol, carbon dioxide, and hot water to produce a higher-quality taste [24,25]. This is because persimmons have an astringent taste [26].…”
Section: Introductionmentioning
confidence: 99%
“…These differences were still found after 81 days (Figure 3c). The color changes that occurred during the drying period were the result of several biochemical reactions, such as degradation of carotenoids, decomposition of other color pigments, and enzymatic and non-enzymatic reactions (Jia et al, 2019). Yamada et al, (2009) suggested that the oxidative and non-oxidative degradation of ascorbic acid would contribute markedly to the browning of this product type, while enzymatic browning, by polyphenol oxidase, and the Maillard reaction, between amino acids and reducing sugars would not play a key role.…”
Section: Daysmentioning
confidence: 99%
“…Tannin insolubilization during the drying process could be associated with structural flesh changes (Figure 2), which happens during natural persimmon fruit ripening (Asgar et al, 2004;Jia et al, 2019;. In astringent cultivars, the ripening process is accompanied by gradual tannin insolubilization, which leads to a progressive decline in ST with subsequent astringency reduction .…”
Section: B)mentioning
confidence: 99%